Peningkatan Kualitas Layanan Jalan Tol Pemalang Batang - Prastiyo, Imam; Dara, Pase (Universitas Kristen Maranatha, 2026)
Road infrastructure plays a vital role in supporting mobility and economic growth. The Pemalang Batang Toll Road, stretching 39.2 km, is part of the Trans Java network, serving as an alternative to the northern coastal (Pantura) route and driving regional economic development. While designed to provide fast and safe access, the toll road faces challenges such as poor road conditions and inadequate nighttime lighting. Despite efforts to meet the Minimum Service Standards (SPM) set by the government, existing conditions still cause user dissatisfaction, as reflected in the high number of accidents in 2022. This study aims to enhance the service quality of the Pemalang Batang Toll Road in accordance with SPM. The research employs a quantitative method, using primary data from questionnaires based on modified service quality (servqual) dimensions and secondary data from literature and regulations. Data analysis was conducted using importance performance analysis (IPA) with SPSS and the analytical hierarchy process (AHP) with expert choice. This study integrates the IPA and AHP methods to assess and prioritize toll road service quality improvements based on the users perspective. The findings show that the toll road’s services are not yet optimal, with seven service attributes placed in quadrant I (priority for improvement). Road surface condition was identified as the top priority for improvement, with a weight value of 42%.